A Research on a Certain Family of Numbers and Polynomials Related to Stirling Numbers, Central Factorial Numbers, and Euler Numbers - J. Y. Kang; C. S. Ryoo (Journal of Applied Mathematics)
Recently, many mathematicians have studied different kinds of the Euler, Bernoulli, and Genocchi numbers and polynomials. In this paper, we give another definition of polynomials Ũn(x). We observe an interesting phenomenon of “scattering” of the zeros of the polynomials Ũn(x) in complex plane. We find out some identities and properties related to polynomials Ũn(x). Finally, we also derive interesting relations between polynomials Ũn(x), Stirling numbers, central factorial numbers, and Euler numbers.